Successful Management of Spontaneous Pneumatocele and Pneumothorax Formation After COVID-19 Infection - Utku Ekin; Christopher Millet; Sohail Chaudhry; Christopher Biggiani; Arslan Chaudhry; Justin Thorson (Annals of Internal Medicine: Clinical Cases)
Pneumatoceles are rarely encountered in the clinical setting. Very few cases have been documented that involved COVID-19 pneumonia as a cause. Furthermore, even fewer cases document spontaneous pneumothorax complicating the pneumatocele that required urgent intervention. We present a case of a patient who developed a pneumatocele as a complication of symptomatic COVID-19 infection. The patient's clinical course was further complicated by spontaneous pneumothorax formation. The patient had thoracostomy and video-assisted thoracoscopic surgery. Here we describe the patient's clinical course in detail.